Stranger Things: Organismal Traits of Two Octocorals Associated With Singular Symbiodiniaceae in a High-Latitude Coral Community From Northern Taiwan - Hsu, Tsai-Hsuan Tony; Carlu, Lilian; Hsieh, Yunli Eric; Lai, Tzu-Yu Angel; Wang, Ching-Wei; Huang, Ching-Yun; Yang, Shan-Hua; Wang, Pei-Ling; Sturaro, Nicolas; Denis, Vianney (Frontiers in Marine Science, 2020)
Scrutinizing the traits of octocorals that could affect their physiological performance becomes increasingly important as several of these species are observed to become dominant on reefs pressured by the Anthropocene. In the present study, we compare the organismal traits of two branching octocorals Litophyton sp. and Stereonephthya sp. commonly populating in sympatry the high-latitude coral communities of northern Taiwan. Using 13 traits, we describe and compare performance traits in these two symbiotic species that we discuss in light of the association they maintain with their algal partners. Litophyton sp. and Stereonephthya sp. hosted Durusdinium and Gerakladium, respectively. Both genera represent singular associations, with the latter further establishing the first solid report of Gerakladium in octocorals. Traits distinguished two groups explained by the two partnerships considered. Litophyton sp. associated with Durusdinium had significantly higher organic matter, chlorophyll (chl) a, total lipid and lower chl c / chl a ratio than Stereonephthya sp. associated with Gerakladium. The δ15N in the host and algae, as well as δ13C in the host were also higher in Litophyton sp. Although no significant difference was observed in the δ13C of the algae, Litophyton sp. presented a significantly higher variance for this trait and for chl a content than Stereonephthya sp. Altogether, the traits examined suggested contrasting performances among the two octocorals. Both octocoral species clearly deviate from an autotrophic diet. Litophyton sp. appears to complement its heterotrophic diet with photosynthetically acquired energy, while Stereonephthya sp. tends to be more specialized and benefits relatively little from its symbiotic relationship. Our study calls for greater consideration of the individual variation in octocoral physiology and in the definition of their ecological strategies.